Frotteuristic Disorders - Ayu Nuzulia Putri; Soetjipto Soetjipto (Faculty of Medicine, Universitas Airlangga, 2020)
Frotteuristic disorders is a rare paraphilia among other paraphilia. Frotteuristic are usually acquired with other paraphilia such as exhibitionism. Frotteuristic disorders is rubbing the genital area on other people to cause orgasm. This action often occurs in public area such as subways, elevators or shopping centers where victims are unaware. Some studies have difficulty getting data on frotteuristic disorders because this sexual harassment rarely reported to the police because there are no witnesses or evidence. This literature reviews aims to determine the comprehensive treatment for frotteuristic disorders.